Myocardial tissue doppler imaging in studying of change in the longitudinal right ventricular function in patients with chronic obstructive pulmonary disease - N. G. Ivanova (Бюллетень сибирской медицины)
The obstructive of paper was to study and match clinical symptoms of chronic obstructive pulmonary disease, laboratory and instrumental analyses data, and data obtained from myocardial Tissue Doppler Imaging. Sixty four patients four patients with chronic obstructive pulmonary disease were examined. It was discovered that information obtained through myocardial Tissue Doppler Imaging is in fact early evidence of pulmonary heart disease available at the pre-clinical stage (functional changes are observed before clinical symptoms).